IOT Based Patient Health Monitoring System - K. V. Sowmya, V. Teju and Yeruva Rajasekhar Reddy (International Journal of Advanced Science and Technology, 2020)
The goal is to calculate and analyze the body temperature and heart beat of a person using IOT. This is mainly used to monitor the health subserviently. The goal of the whole paper is to establish a cosmologically appropriate framework for understanding the health care system and to suggest regular treatment for patients with incessant diseases. When the individual has a sleeping pad illusion and such systems are enormous and better accessible throughout therapeutic emphasis in ICU, the clear observatory frameworks will unmistakably be utilized. The shape is made of house use by patients who, with the specialist or family guides, are not yet in a fundamental condition. The aim of this paper is to establish a magical system structured for the review of health professionals and to give routine solutions to patients with persistent contaminations.